In vivo dosimetric impact of breast tissue expanders on post‐mastectomy radiotherapy. Issue 1 (27th October 2015) - Gee, Harriet E; Bignell, Fiona; Odgers, David; Gill, Simran; Martin, Darren; Toohey, Joanne; Carroll, Susan
Abstract: Introduction: Temporary tissue expanders with metallic ports for gradual saline injection are increasingly employed to facilitate breast reconstruction after post‐mastectomy radiotherapy (PMRT). Treatment beams therefore pass through a high‐density rare‐earth magnet. Measurements ex vivo suggest attenuation of dose to the skin and chest wall at clinical risk of relapse. The purpose of the study was to quantify the resulting dose reduction in vivo, compared with treatment planning system (TPS). Methods: Sixteen patients receiving PMRT had in vivo dosimetry prospectively performed with ethics board approval. Port was located within the expanded chest wall using the planning CT scan. Strips of radiochromic film were laid on the skin surface underneath the bolus. To aid interpretation, ex vivo measurements were also performed, including comparison with TPS predictions. Results: An average 7% reduction in dose to skin surface was measured in 15 of 16 patients. This was reproducibly located in the 'shadow' of the magnet, corresponding to each of the paths of the medial and lateral tangents. The average area was 1.07 cm 2 (range 0.39 cm 2 to 2.36 cm 2 ). E x vivo measurements confirmed attenuation of the beam in the shadow of the port. The surface area of the 'cold‐spot' varied with angle of the beam relative to the metallic port. Dose attenuation in vivo differed from that predicted by the TPS. Conclusion: Dose is attenuated in the 'shadow' of the tissue expander port in patients receiving PMRT. This is likely to be clinically insignificant for most, but centres should undertake appropriate measurements before utilising TPS predictions.